Manufacturing of hourglass-shaped through holes with varying diameters at different depths by dual-pulse laser drilling and laser-induced plasma-hole interaction. (April 2018) - Liu, Ze; Wu, Benxin; Samanta, Avik; Shen, Ninggang; Ding, Hongtao; Shin, Yung C.
Abstract: Microholes in a metal with diameters varying unusually at different hole depths (e.g., microholes with a decreasing and then increasing diameter with the depth) have important applications. This paper reports studies on a novel method of drilling such microholes in a metal, which is through "double-pulse" percussion laser drilling followed by laser-induced plasma (from a backing plate placed behind the workpiece) – hole interaction. Using this method, a through microhole has been produced in a metal workpiece, which has similar diameters at the hole entrance and exit, but a much smaller diameter at a certain waist section inside the hole.